2016
DOI: 10.3835/plantgenome2015.09.0084
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of Two Wheat Powdery Mildew Resistance Genes Located at the Pm1 Cluster

Abstract: Powdery mildew caused by Blumeria graminis (DC.) f. sp. tritici (Bgt) is a globally devastating foliar disease of wheat (Triticum aestivum L.). More than a dozen genes against this disease, identified from wheat germplasms of different ploidy levels, have been mapped to the region surrounding the Pm1 locus on the long arm of chromosome 7A, which forms a resistance (R)-gene cluster. Mlm2033 and Mlm80 from einkorn wheat (T. monococcum L.) were two of the R genes belonging to this cluster. This study was initiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…dicoccoides (tetraploid). Intriguingly, Liang et al (2016) did observe strong recombination suppression in this region of two T. monococcum accessions (diploid). It could be possible that an ancient introgression(s) predisposed this region to its present structure, which in turn promoted a diversification of NLRs that culminated in the linked resistance cluster carrying Pm1a and Sr15-Lr20.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…dicoccoides (tetraploid). Intriguingly, Liang et al (2016) did observe strong recombination suppression in this region of two T. monococcum accessions (diploid). It could be possible that an ancient introgression(s) predisposed this region to its present structure, which in turn promoted a diversification of NLRs that culminated in the linked resistance cluster carrying Pm1a and Sr15-Lr20.…”
Section: Discussionmentioning
confidence: 89%
“…It was suggested that all the genes sharing the marker interval with Pm1 were allelic to Pm1. However, Liang et al (2016) showed that et al, 2018) was concluded to occupy the same locus as PmU (Zhang et al, 2018), within the same interval as Pm1. However, sequence comparison of Pm1a with Pm60 showed they were quite dissimilar (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Axminster is quite dissimilar to Pm60, therefore, it is unlikely that they represent orthologous genes (Hewitt et al 2020). These ndings suggest that an R-gene cluster is present within this genomic region of cultivated and wild wheat species of different ploidy levels, conferring powdery mildew resistance (Liang et al 2016;Zhang et al 2018). Recently, a multi-genome comparisons showed huge differences in NLR content between wheat genotypes; Among ~ 2,500 loci with NLR signatures identi ed in the 16 wheat cultivars, 31-34% of them are shared across all genomes, while the number of unique signatures ranged from 22 to 192 per cultivar (Walkowiak et al 2020).…”
Section: Introductionmentioning
confidence: 82%
“…The QPm.GZ1-7A was mapped to a large region of chromosome 7AL (144 Mb). So far, about 20 Pm genes have been localized on chromosome 7AL: Pm1 consisting of five different alleles: Pm1a, Pm1b, Pm1c (Pm18), Pm1d (Hsam et al, 1998), and Pm1e (Pm22; Singrün et al, 2003), Pm9 (Schneider et al, 1991), mlRd30 (Singrün et al, 2004), Pm37 (Srnić et al, 2005;Perugini et al, 2007), NC96BGTA4 (Srnić et al, 2005), MlIW172 (Ouyang et al, 2014), PmU (Qiu et al, 2005), NCA6 (Miranda et al, 2007), Mlm2033 and Mlm80 (Yao et al, 2006;Liang et al, 2016), MlIw72 (Ji et al, 2007), MlAG12 (Maxwell et al, 2009), MlWE18 (Han et al, 2009), PmG16 (Ben-David et al, 2010, PmTb7A.1 and PmTb7A.2 (Chhuneja et al, 2011), HSM1 (Li et al, 2013), MlUM15 (Worthington et al, 2014, Pm59 (Tan et al, 2018), and QPm.gb-7A (Desiderio et al, 2021). According to Desiderio et al (2021), most of these genes are likely to be closely linked and create clusters.…”
Section: Discussionmentioning
confidence: 99%